Hypothermia during Surgical Treatment of Type A Aortic Dissection: A 16 Years’ Experience - Francesco Macrina; Maria Cristina Acconcia; Luigi Tritapepe; Mizar D’abramo; Wael Saade; Alessandra Capelli; Fabio Miraldi (International Journal of Vascular Medicine)
Acute aortic dissection (AAD) is among the most challenging cases for surgical treatment and requires procedural expertise for its safe conduct. Aortic surgery has undergone several changes over the last years, especially concerning cerebral protection. The brilliant results obtained with the aid of selective anterograde cerebral perfusion led to a progressive increase of circulatory arrest temperature, with the rise of safe time along with a reduction of the extracorporeal circulation time and hypothermia-related side effects. However, there is still no definitive consensus concerning the optimal range of temperature to be used during circulatory arrest. Objectives. This is a retrospective observational study, and we examined 16-year trends in the presentation, diagnosis, hospital outcome and treatment of A AAD type. In our Cardiac Surgery Unit in Policlinico Umberto I of Rome, our analysis focused on patients, who received ACP during aortic surgery and we analyzed the differences between two distinct groups based on the lowest temperature reached during CPB conduction: Lower Temperature Group (LT) (T < 24°C) versus Higher Temperature Group (HT) (T ≥ 24°C) arrest circulation temperature. Methods. Data from 241 patients enrolled between August 2002 and March 2018 were analyzed. Patients were divided according to the lowest temperature reached into 2 groups: Lower Temperature group (LT) (94 patients) and Higher Temperature Group (HT) (147 patients). Results. Our results showed a significant reduction of in-hospital mortality and in-hospital results in patients with higher CPB temperature. The global incidence of complications was statistically reduced in HT group: we found a statistical significant reduction of intestinal ischemia, and a similar trend also for other complications analyzed, such as infections. Since the two groups were similar for type of surgical procedures, we considered these differences depending on the lower temperature value reached, according to the current literature. Conclusions. We found a significantly higher mortality in patients with lower temperature during CPB and a global reduction of complications and in particular a significant reduction of intestinal ischemia in patients with higher temperature during CPB. We found a similar trend in other fields of investigations, so we can conclude that circulatory arrest performed at temperature ≥24°C nasopharyngeal temperature associated with ACP is a safe strategy for aortic surgery for AAD.